2020
DOI: 10.1111/tbed.13611
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever in Latvian wild boar—A step closer to elimination

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 21 publications
(52 reference statements)
5
59
0
Order By: Relevance
“…The last outbreak in a pig farm was reported in July 2019, with 10 reports of ASF in pig farms in 2018 (Disease information-Immediate notifications 2005-2020), but reports of infected wild boars continued into 2020. An evaluation of the current epidemiological situation in wild boars indicated a decrease in active circulation of the virus and suggested that managing the wild boar population to keep numbers as low as possible, continuing surveillance and removal of wild boar carcasses could result in elimination of the infection (Olsevskis et al 2020). An experimental oral vaccine developed from a field strain of reduced virulence recovered from a wild boar in Latvia was reported to show promise (Barasona et al 2019).…”
Section: Latviamentioning
confidence: 99%
See 1 more Smart Citation
“…The last outbreak in a pig farm was reported in July 2019, with 10 reports of ASF in pig farms in 2018 (Disease information-Immediate notifications 2005-2020), but reports of infected wild boars continued into 2020. An evaluation of the current epidemiological situation in wild boars indicated a decrease in active circulation of the virus and suggested that managing the wild boar population to keep numbers as low as possible, continuing surveillance and removal of wild boar carcasses could result in elimination of the infection (Olsevskis et al 2020). An experimental oral vaccine developed from a field strain of reduced virulence recovered from a wild boar in Latvia was reported to show promise (Barasona et al 2019).…”
Section: Latviamentioning
confidence: 99%
“…In Belgium and Czech Republic it was possible to eradicate the infection (Marcon et al 2020), which in both cases could be restricted to a limited area. However, Estonia and Latvia, where the whole countries were infected, the combination of surveillance for and burial of wild boar carcasses and population reduction due both to ASF and to increased hunting pressure has resulted in a demonstrable decline in virus circulation (Schulz et al 2019;Olsevskis et al 2020).…”
Section: Managing Asf In Free-living Wild Boar or Feral Pig Populationsmentioning
confidence: 99%
“…In case of a longer-lasting epidemic like in Estonia and Latvia, a decrease of ASFV prevalence estimates were observed, whereas the prevalence of wild boar being seropositive increased within both countries [9,11,12]. It is hypothesized that this course indicates the decline of circulating ASFV and a country obtaining such results might be on its way of disease elimination [9,11,12]. In a previous study, Lithuanian surveillance data from 2014 to 2017 yielded a clear increase in the ASFV prevalence estimates in wild boar found dead (from 20.1% in 2014 to 79.68% in 2017) whereas the average seroprevalence during 2014-2017 was low (0.45%) suggesting that the ASF epidemic in Lithuania was still in full progress by 2017 [1].…”
Section: Open Accessmentioning
confidence: 99%
“…Similar to previous studies [9,11,12], for analyses, samples were grouped depending on their laboratory results.…”
Section: Prevalence Estimationsmentioning
confidence: 99%
“…By contrast, seropositive animals survived the infection and were able to eliminate the virus [ 10 ]. Accordingly, it has been hypothesized that an increase in seropositive wild boar among all sampled wild boar might indicate a subsiding epidemic [ 11 , 12 , 13 ]. However, studies that prove the lack of infectiousness of these animals or the possibility of reactivation of ASFV are still missing.…”
Section: Thesesmentioning
confidence: 99%